2012
DOI: 10.1007/s11033-012-1754-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of STAT4 rs7574865 polymorphism with autoimmune diseases: a meta-analysis

Abstract: The association between the signal transducer and activator of transcription 4 (STAT4) gene rs7574865 single nucleotide polymorphism and different autoimmune diseases remains controversial and ambiguous. We conducted this study to investigate whether combined evidence shows the association between STAT4 rs7574865 polymorphism and autoimmune diseases. Comprehensive Medline search and review of the references were used to get the relevant reports published before September 2011. Meta-analysis was conducted for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 73 publications
1
39
0
1
Order By: Relevance
“…The rs7574865 SNP is one of the most frequently examined polymorphisms in the STAT4 gene and its function is related to gene expression on a transcriptional level and splice variation (Liang et al, 2012). The T allele of this particular SNP has been associated with multiple autoimmune disorders but the association is dependent on the population examined (Lee et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rs7574865 SNP is one of the most frequently examined polymorphisms in the STAT4 gene and its function is related to gene expression on a transcriptional level and splice variation (Liang et al, 2012). The T allele of this particular SNP has been associated with multiple autoimmune disorders but the association is dependent on the population examined (Lee et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients with APSIII may also be diagnosed with celiac disease (CD). Despite the genetic variation in human leukocyte antigen (HLA) and its involvement in T1D development, new genes have been identified as potentially important in disease's susceptibility and modulation outside HLA range (Gillespie, 2006;Liang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,22 Genome-wide association studies have implicated STAT4 in diseases such as asthma, IBD, RA and SLE [23][24][25] and IL23R in IBD, psoriasis and RA. [26][27][28][29] Our data provide a link between a T cell-extrinsic role for STAT4 in mediating IL-23 responsiveness to memory T helper and NKT cells, and IL-17 production.…”
Section: E955393-4mentioning
confidence: 99%
“…The rs7574865 G/T SNP occurs in intron 3 of STAT4 gene, and has been associated with juvenile idiopathic arthritis (JIA) in non-Hispanic white population 5 . Genome-wide association study (GWAS) and a meta-analysis have reported that STAT4 rs7574865 T allele confers susceptibility to JIA, SLE, rheumatoid arthritis (RA), type 1 diabetes (T1D), systemic sclerosis (SSc), primary antiphospholipid syndrome (APS), inflammatory bowel diseases-ulcerative colitis (IBD-UC), and primary Sjogren's syndrome (pSS) 6,7 . Moreover, the minor C allele of STAT4 rs7601754 SNP was shown to be a protective allele in SLE, whereas the major T allele might be a risk allele for SLE susceptibility 8 .…”
mentioning
confidence: 99%